Pregnancy in infertility couples. Experience at Rebagliati Martins National Hospital, EsSalud - Pacheco Romero, José (2015)
OBJETIVES: To determine the pregnancy rate in a population of couples being treated for infertility or reproductive loss, the most common pathology in these couples and the time of the study or treatment that the woman came to conceive. DESIGN: Retrospective, observational, descriptive, clinical study. PLACE: Human Reproduction Unit of the Assistance Network Rebagliati, EsSalud, based university teaching. MATERIALS AND METHODS: We reviewed the medical histories of all the couples being treated for infertility or reproductive loss doctors Unit in 2004, determining their characteristics, factors related to the problem of reproduction, study and treatments carried out, pregnancies and time the study and treatment of the pregnancy occurred. RESULTS: In 2004, 564 new partners, of which 218 hatched, with a pregnancy rate of 38.6% were met. The factors involved in couples who conceive were reached in 68.7% tubal, ovarian 41.2%, 29.4% male and 27% uterus. Near lamitad of women who conceived did before becoming underwent surgery; 5% did so after hysterosalpingography, 5.2% after the postcoital test and 18.5% conceived while waiting for an operating shift. In 19.9% of patients, the pregnancy occurred after the single surgery, especially after a laparoscopy accompanied hysteroscopy. Another 28.4% of women conceived after surgery followed by induction of ovulation, making a total of 48.3% of women who gave birth after the diagnostic and therapeutic surgery. Conclusions: The pregnancy rate of 38.6% is one of the highest reported in the literature, and does not include assisted fertilization techniques. We believe that the result is related to teamwork, implementation of agreed clinical guidelines, interest of couples in their study, hospital equipment and materials and training satisfactory, permanent teaching and research.